2020
DOI: 10.3390/ijerph17186552
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Socio-Demographic, Clinical and Biochemical Parameters with Healthcare Cost, Health- and Renal-Related Quality of Life in Hemodialysis Patients: A Clinical Observational Study

Abstract: We examined factors associated with healthcare cost, health-related quality of life (HRQOL), and kidney disease quality of life (KDQOL) in hemodialysis patients. We conducted a cross-sectional study on 160 patients from January to April 2019 at a hemodialysis center. Socio-demographic, clinical, and laboratory parameters and quality of life (QOL) (using KDQOL-SF-v1.3) were assessed. Monthly healthcare costs were extracted from the hospital information system. The means of healthcare cost, HRQOL, and KDQOL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
3
9
2
1
Order By: Relevance
“…Our study showed that total cumulative cost of CKD patients was high. This has also been confirmed by previous studies [ 11 18 ]. The most important contributors for total health care cost in CKD patients were cardiovascular hospitalizations (admissions and hospital stay), particularly HF and CKD hospitalizations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that total cumulative cost of CKD patients was high. This has also been confirmed by previous studies [ 11 18 ]. The most important contributors for total health care cost in CKD patients were cardiovascular hospitalizations (admissions and hospital stay), particularly HF and CKD hospitalizations.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, CKD represents a major and growing economic problem [ 3 , 11 , 12 ]. Increasing the knowledge about CKD-related costs is mandatory to ascertain how CKD management can be improved, leading to a significant decrease in CKD burden [ 5 , 11 18 ]. Unfortunately, data about the impact of CKD on health care costs in Spain are scarce, and most importantly, not focused on a comprehensive approach [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have shown an association with comorbidities [23,29], some describe that hypertension and diabetes were associated with worse results regarding pain and work status aspect and have been found to a ect the QoL more broadly [13,32]. Our study found no association between hypertension or diabetes and KDQOL parameters.…”
Section: Discussioncontrasting
confidence: 59%
“…Some authors have found better QoL scores in elderly patients, suggesting that 'patients' understanding of the disease, the acceptance of their limitations, and decreased emotional ability are possible explanations for this association [27,28]. Some studies have found increased levels of QoL in younger years than in older years [17,29], with similar results in studies in Nepal and Saudi Arabia [17,30,31]. The lack of consistency in the ndings suggests that more studies are required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adverse emotions, the responsibility nursing group scored lower in SAS and SDS scores than the routine nursing group. Objectively speaking, the medical expenses of hemodialysis are relatively expensive, and the treatment process is long, which brings a burden to the family economy of hemodialysis patients [23]. On the contrary, the whole treatment process will also cause psychological pressure on the patients, which is prone to induce anxiety and depression in patients, resulting in decreased treatment compliance.…”
Section: Discussionmentioning
confidence: 99%